The struggle of Hagar : explorations toward a Filipino theology of household - Mella, Connie Semy P. (Metro Manila : South East Asia Graduate School of Theology, 2005)
This study was conducted for the purpose of exploring how to develop a Filipino theology of household by looking at the potentials of meaning of the family story in Genesis 16:1-16 and Genesis 21: 8-21. The narrative criticism and the descriptive methods of research were used whereby the text was read a story. Its thematic line, plot, characterizations, symbols, use of narration and dialogue, and biblical type-scenes were critically analyzed. It also described the current condition, the issues and challenges the Filipino family is facing today, including the migration phenomenon and its implication to the Filipino household. "What is the foundational sustaining and critical role of Hagar's story in the development and formulation of a Filipino theology of household?
In partial fulfillment of the requirements for the Degree Master of Theology
A thesis presented to the faculty of the South East Asia graduate School of Theology